Latency hiding in consistent, large scale, distributed virtual environments - Du, Jiang. (2008)
A Distributed Virtual Environment (DVE) allows a group of geographically dispersed users to interact in real time. To provide a usable system, interactions with objects and other users must be observed by participants with sufficient consistency and within a limited delay. However, in a Wide Area Network (WAN), there can be considerable communication delays between different users. The delay cannot be eliminated entirely, but can only be minimized. However, we cannot minimize or eliminate the transmission delay caused by hardware. The main effects will be in the visual mode of the environment, where delays can cause discontinuous state changes and jumps in the positions of objects. In this project we aim to handle such situations and try to minimize such negative effects. The overall goal of this project is to create an environment with consistency in which users are unaware that the system is distributed over a network, whether a LAN or the Internet, by reducing the effect caused by time delays.